2021
DOI: 10.1007/s10072-021-05065-w
|View full text |Cite
|
Sign up to set email alerts
|

Tics in patients with encephalitis

Abstract: Background Movement disorders have been described in the context of different types of encephalitis. Among hyperkinetic manifestations, tics have sporadically been reported in cases of encephalitis resulting from a range of aetiologies. Objective This review aimed to assess the prevalence and characteristics of tics in patients with encephalitis. Methods We conducted a systematic literature review of original studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…The prevalence and characteristics of tics in patients with encephalitis were reviewed in a systematic study, which found that sporadic cases of tics were associated with encephalitis, particularly during a post-encephalitis period, and with basal ganglia involvement 54 . A case-control autopsy study (of nine individuals with TS) using basal ganglia transcriptome by RNA sequencing in the caudate and putamen found disrupted basal ganglia neuronal signaling 55 .…”
Section: Etiologymentioning
confidence: 99%
“…The prevalence and characteristics of tics in patients with encephalitis were reviewed in a systematic study, which found that sporadic cases of tics were associated with encephalitis, particularly during a post-encephalitis period, and with basal ganglia involvement 54 . A case-control autopsy study (of nine individuals with TS) using basal ganglia transcriptome by RNA sequencing in the caudate and putamen found disrupted basal ganglia neuronal signaling 55 .…”
Section: Etiologymentioning
confidence: 99%